The potential of new skills competencies in the field of games at vocational high school - Albari, Fardan Barkah; Abulkhoir, Muhammad Azhar; Augustianingrum, Nurul Khofifah; Ananda, Rizky (Jurnal Pendidikan Teknologi Kejuruan, 2021)
Vocational High School is a formal education that organizes vocational education at the senior secondary level which aims to prepare individuals to be ready for work. In this 4.0 industrial revolution, Indonesia needs a lot of human resources. The game industry has grown by 9-12%. This shows that there is an opportunity in this gaming industry. The gaming industry is a mix of art and technology. Therefore, people who are skilled in the arts and technology are needed. This research method uses descriptive methods and qualitative analysis. As reported by CNBC (2019), Bekraf requires a digital workforce of around 600 thousand per year and this cannot be fulfilled. This shows the high demand from the digital industry. The survey results released by Bekraf show that the game industry is an industry that is aggressively innovating. There are also very many game enthusiasts in Indonesia. Game players from in Indonesia are ranked 16 in the world. In 2015, high school graduates or equivalent dominated the workforce in the creative industry, especially digital. This shows that SMK graduates have a great opportunity to develop the game industry in Indonesia.